(untitled) (Health and Biosciences, 2021)
Family farming accounts for a considerable part of food production and, consequently, of domestic supply and is largely responsible for making up the basic diet of the Brazilian. The National School Feeding Program aims to transfer financial resources to municipalities, designed to partially meet the nutritional needs of students in the Brazilian public network. The financial resources are of compulsory use in the purchase of foodstuffs and aim at maintenance and respect to the regional alimentary habits and agricultural vocation of the municipality. In order to complete this purchase, Federal Law No. 11,947 was enacted, regulating one more institutional area for the commercialization of Family Agriculture products. The objective of this study was to outline the socioeconomic, demographic, living and working conditions of family farmers who offer their products for school feeding. 78 family farmers participated in the study and found a significant association between income increase and improvement of the living conditions of family farmers and improvement in planting and feeding. It was concluded that the laws and resolutions of the PNAE have brought considerable advances in the life of the family farmers who sell to the program due to the possibility of improving their living conditions by increasing their production or diversification, of the market and the improvement of the feeding of the familiar farmer and his relatives.